Primary Carcinoma of the Fallopian Tube: A Review of a Single Institution Experience of 8 Cases. (13th February 2014) - Nanaiah, Shakuntala P.; Rathod, Praveen S.; Rajkumar, Namrata N.; Kundargi, Rajshekar; Subbian, Anbukkani; Ramachandra, Pallavi V.; Krishnappa, Shobha; Narayan, Abhilasha; Devi, Uma K.; Uttamchand, Bafna D.
Abstract : Aims and Objectives . To evaluate the clinicopathologic features, response to cytoreductive surgery and adjuvant platinum-based chemotherapy with or without paclitaxel. Materials and Methods . A retrospective observational study of 8 women with a histopathologic diagnosis of primary fallopian tube carcinoma (PFTC) from January 2000 to February 2013. Results . 4/8 (50%) of the women were in the early stage and an intraoperative frozen section was 100% effective in identifying fallopian tube carcinoma and then a staging laparotomy was performed. All 4/8 cases in the early stage had received and responded to single agent carboplatin and all are alive without clinical, radiological, or biochemical evidence of recurrence at the end of 2 years and the longest survivor has completed 13 years. Primary optimal cytoreductive surgery was achievable in 3/4 (75%) in advanced disease. All showed response to adjuvant paclitaxel and carboplatin (T+C), but all had succumbed to the disease following recurrence with mean progression-free survival of 19 months (range 15–21 months) and mean overall survival of 27 months (range 22–36 months). Conclusion . The pivotal role played by a frozen section in diagnosing PFTC which is rare needs to be reemphasized, therefore justifying a primary staging laparotomy in an early stage. Prolonged survival observed in this group following an optimum tailored adjuvant single agent carboplatin is worth noting.